2022
DOI: 10.4049/jimmunol.208.supp.59.14
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and mucosal IgA responses are variably induced in response to SARS-CoV-2 mRNA vaccination and are associated with protection against subsequent infection

Abstract: SARS-CoV-2 is a novel respiratory virus that has quickly spread across the globe. The virus uses a protein called Spike and its associated receptor binding domain (RBD) to interact with angiotensin converting enzyme-2 (ACE-2) on the surface of epithelial cells in the respiratory tract. Although a definite correlate of protection against COVID-19 has yet to emerge, many studies have quantified anti-Spike and anti-RBD IgG antibody (Ab) levels, as well as neutralizing Ab in the blood to ascertain immunity. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…After vaccination, Spike, Spike/NTD and Spike/RBD positively correlated with neutralizing antibodies, as observed in other cohorts (45), but we also noticed a positive correlation with Spike/NTD in saliva. In previous studies, a detectable neutralizing activity in saliva observed 2 to 4 weeks post-vaccination was described low and transient with a rapid decline (16, 47). The ratio of saliva/serum IgA clearly showed two differential profiles according to previous COVID-19 status.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…After vaccination, Spike, Spike/NTD and Spike/RBD positively correlated with neutralizing antibodies, as observed in other cohorts (45), but we also noticed a positive correlation with Spike/NTD in saliva. In previous studies, a detectable neutralizing activity in saliva observed 2 to 4 weeks post-vaccination was described low and transient with a rapid decline (16, 47). The ratio of saliva/serum IgA clearly showed two differential profiles according to previous COVID-19 status.…”
Section: Discussionmentioning
confidence: 88%
“…Vaccination with mRNA or Adenovirus-vectored vaccines reactivated a mucosal response in previously infected individuals but failed to induce a significant mucosal response in naive individuals, as already observed on a more limited cohort (25). As breakthrough infections have been correlated with IgA levels (16), IgA production may be a key point to address the issue of controlling the infection locally and preventing the transmission from vaccinated individuals. Most efficient vaccine platforms or route of administration inducing mucosal immunity are needed in the future for COVID-19 control, as already shown in preclinical studies (7, 9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation